Формули достовірності в демонологічних переказах - Рудан, Е. (Народна творчість та етнологія, 2011)
There are certain units of text, that specify on veracity represented or demonstrate a faith in veracity. These units of text we will name the formulas of authenticity and will try to ground essence of this term, define, what types of formulas of authenticity are used in demonology translations, what method retell and retell incarnate them in, and also the function of persuasion comes in what method true.